Role of Commercial Cucumber on Income Generation in Kathmandu Valley - Mulmi, Ujjwala; Rajbhandari, Binayak P. (Nepalese Journal of Agricultural Sciences, 2026)
The study was conducted to assess the commercial cucumber production and its role in income generation in Kathmandu Valley. In the study area chemical inputs were widely applied with (92.38%) using insecticides, (57.14%) using fungicides and (38.10%) were using both chemical and bio-pesticides. In terms of irrigation majority farmers depended on canal (42.46%) and tube well (35.24%) while thedrip irrigation method was limited. Regarding productivity, the average cucumber yield was 740 kg per ropani and average net income was Rs 2070 resulting in a benefit cost ratio exceeding 1. Pest and disease infestation, high input cost, fluctuating market price, limited irrigation facilities and middle men exploitation were major problem in cucumber production in study area. To address these challenges, farmers must practice use of balanced input through Integrated Nutrient Management and Integrated Pest Management farmers must be trained on record keeping and benefit cost analysis for better decision making